Relação entre presença de anticorpos anti-leishmania spp. e carga parasitária em sangue de cães de área endêmica para leishmaniose visceral - Beloti, Carolina Aparecida Carlin [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Visceral leishmaniasis (VL) control strategies in Brazil are based on the early detection and treatment of the patients, vector control by insecticide and the serological screening and euthanasia of positive dogs. Thus, canine visceral leishmaniasis (CVL) diagnosis must accurately identify canine reservoir hosts to ensure the efficiency of screening. Considering that the humoral immune response of dogs to natural Leishmania spp. infection is dependent on parasite load, our aim was to evaluate if outcomes of the diagnostic kits currently used in canine seroepidemiological surveys in Brazil (DPP-BioManguinhos™ rapid test and EIA-ELISA Indirect ELISA BioManguinhos™) could be related to the blood parasite loads in dogs. Six hundred and 10 dogs from the VL endemic region of Northwest São Paulo State were sampled for this evaluation. Positivity varied from 15.9 to 68.4% between diagnostic techniques, due to differences in test sensitivity and specificity. Overall, positive dogs had higher mean parasite loads than negative dogs. Nevertheless, the potential of transmission of the negative dogs shall be investigated
Keywords: Reação em cadeia da polimerase; Cão; Ensaio de imunoadsorção enzimática; Diagnostico; Leishmania; Leishmaniose visceral; Rapid test DPP(TM)